REKOMENDASI CALON KARYAWAN TETAP DI PERUSAHAAN J&T EXPRESS DENGAN METODE SIMPLE ADDTIVE WEIGHTING - Prabu Alif Anggadiputra; Viny Christanti Mawardi; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The definition of an expedition is the delivery of goods or a company that transports goods. Expeditions for shipping goods are now often found in Indonesia because of the large number of people who make transactions via online. There is a J&T Express expedition service which is one of the shipping services that is able to serve deliveries within cities, between cities and between provinces. J&T Express has problems in determining permanent warehouse employees. The determination of warehouse employees for permanent employees at J&T Express is still done individually by the Supervisor of each J&T Express branch. The Simple Additive Weighting method is one method to make it easier for Supervisors to choose permanent warehouse employees with rankings. The way it works is that the user selects the 7 criteria provided, namely performance, attendance, manners, appearance, ability, knowledge, and responsibility.